State-dependent interactions in ultracold 174Yb probed by optical clock spectroscopy. (1st November 2017) - Franchi, L; Livi, L F; Cappellini, G; Binella, G; Inguscio, M; Catani, J; Fallani, L
Abstract: We report on the measurement of the scattering properties of ultracold 174 Yb bosons in a three-dimensional optical lattice. Site occupancy in an atomic Mott insulator is resolved with high-precision spectroscopy on an ultranarrow, metrological optical clock transition. Scattering lengths and loss rate coefficients for 174 Yb atoms in different collisional channels involving the ground state 1 S0 and the metastable 3 P0 states are derived. These studies set important constraints for future experimental studies of two-electron atoms for quantum-technological applications.